A Comparative Pharmacokinetics Study of the Anti-Parkinsonian Drug Pramipexole - Ratih S. I. Putri; Effi Setiawati; Syifa A. Aziswan; Fenny Ong; Raymond R. Tjandrawinata; Liana W. Susanto (MDPI AG, 2016)
The present study aimed to compare pharmacokinetic parameters of two pramipexole 0.25 mg formulations in order to show bioequivalence. The study was conducted in a randomized, open-label, two-period, two-sequence, and crossover design, involving 23 healthy volunteers. One of the 0.25 mg formulations of pramipexole evaluated in the study was manufactured by PT Dexa Medica, Palembang, Indonesia, the other, used as the reference, by Boehringer Ingelheim Pharma GmbH & Co. KG, Ingelheim am Rhein, Germany. All eligible subjects were required to fast before each drug administration period, which was separated by a one-week washout period. Pramipexole concentrations in plasma were assayed using a validated ultra performance liquid chromatography with mass spectrometry (UPLC-MS/MS) detector. The evaluated pharmacokinetic parameters included the area under the plasma concentration curve from time zero to the last observed measurable concentration (AUC0-t), the area under the plasma concentration curve extrapolated to infinite time (AUC0-∞), the maximum plasma concentration (Cmax), the time to reach Cmax (tmax), and the plasma concentration half-life (t1/2). To evaluate the bioequivalence of those two pramipexole formulations, 90% confidence intervals (CIs) for geometric mean ratios of both formulations were calculated for AUC and Cmax parameters, while tmax and t1/2 differences were analyzed on the non-transformed data using Wilcoxon matched-pairs and a Student's paired t-test, respectively. The 90% CIs for the geometric mean ratios of the two pramipexole formulations were 95.89% (90.73%-101.34%), 95.53% (89.75%-101.68%), and 92.11% (84.35%-100.58%) for AUC0-t, AUC0-∞, and Cmax, respectively. There were no statistically significant differences for tmax and t1/2 between the two pramipexole formulations. It is concluded that two pramipexole formulations in this study were bioequivalent.